2013
DOI: 10.1371/journal.pone.0085179
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prostatitis in Prostate Cancer: Meta-Analysis

Abstract: ObjectiveUse systematic review methods to quantify the association between prostatitis and prostate cancer, under both fixed and random effects model. Evidence AcquisitionCase control studies of prostate cancer with information on prostatitis history. All studies published between 1990-2012, were collected to calculate a pooled odds ratio. Selection criteria: the selection criteria are as follows: human case control studies; published from May 1990 to July 2012; containing number of prostatitis, and prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 38 publications
9
74
0
3
Order By: Relevance
“…The prognostic and therapeutic implications of our findings, together with the findings of Dennis et al and Jiang et al (6,7), may be of considerable importance. In this respect, it might be interesting to investigate whether aggressive therapeutic management of chronic prostatitis syndromes may have cancer-preventive potential.…”
Section: Clinical Implications and Key Pointssupporting
confidence: 68%
See 2 more Smart Citations
“…The prognostic and therapeutic implications of our findings, together with the findings of Dennis et al and Jiang et al (6,7), may be of considerable importance. In this respect, it might be interesting to investigate whether aggressive therapeutic management of chronic prostatitis syndromes may have cancer-preventive potential.…”
Section: Clinical Implications and Key Pointssupporting
confidence: 68%
“…At the clinical level, a number of studies investigated whether a history of clinical prostatitis may increase the risk of developing prostate cancer. The results of these studies have been meta-analyzed by Jiang et al (6). This work, based on a literature search performed up to July 2012, confirmed previous findings (7) and indicated that clinical prostatitis may be significantly associated with prostate cancer.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…It has been proposed that chronic inflammatory infiltrate-positive prostatitis may protect against prostate cancer (8). The majority of previous studies included patients with diagnosis of prostate cancer and controls from patients records or interviews (1,2,9). By contrast, the present study used a randomly selected sample of Finnish men surveyed in the 1990s to evaluate the effect of prostatitis on prostate cancer incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous meta-analyses provided significant evidence of the association between prostatitis and prostate cancer (1,2). There are, however, several studies showing no association or a negative correlation between prostatitis and prostate cancer (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%